2019
DOI: 10.1002/mp.13344
|View full text |Cite
|
Sign up to set email alerts
|

Robust optimization for intensity‐modulated proton therapy with soft spot sensitivity regularization

Abstract: Purpose Proton dose distribution is sensitive to uncertainties in range estimation and patient positioning. Currently, the proton robustness is managed by worst‐case scenario optimization methods, which are computationally inefficient. To overcome these challenges, we develop a novel intensity‐modulated proton therapy (IMPT) optimization method that integrates dose fidelity with a sensitivity term that describes dose perturbation as the result of range and positioning uncertainties. Methods In the integrated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Because robust optimization is not explicitly incorporated in either framework, it is an area for future research. We recently developed a sensitivity regularization method to improve the robustness of IMPT plans against range and setup uncertainties 27,31 . This sensitivity‐regularized robust optimization method is computationally efficient and resilient to worse‐than‐expected errors.…”
Section: Discussionmentioning
confidence: 99%
“…Because robust optimization is not explicitly incorporated in either framework, it is an area for future research. We recently developed a sensitivity regularization method to improve the robustness of IMPT plans against range and setup uncertainties 27,31 . This sensitivity‐regularized robust optimization method is computationally efficient and resilient to worse‐than‐expected errors.…”
Section: Discussionmentioning
confidence: 99%
“…The combined effects of spreading out distal edges and the random uncertainties of individual beams may be patient specific and need to be carefully assessed in future work. In addition, we have proposed an integrated robust BOO framework for IMPT, 15 which generates robust beam orientation and robust fluence map efficiently in a single step. Sensitivity regularization and heterogeneity weighting were added to the group sparsity‐based BOO framework to encourage robustness.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the dose conformity, the plan robustness can improve as well. We showed that beams from different angles could be compensatory toward range and positioning uncertainties 13,15 . On the other hand, using a larger number of beams in IMPT can be impractical.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The plan robustness is better maintained at the cost of substantially increased computational cost . To avoid the additional burden of calculating the worst cases and provide the robustness consideration as a soft constraint, we recently modeled the scanning spot sensitivity concerning range and positioning uncertainties as a regularization term in the optimization . We showed improved dosimetry, robustness to larger range uncertainties, and an order of magnitude faster optimization time than the worst case approach.…”
Section: Introductionmentioning
confidence: 99%